Balancing financial incentives during COVID-19: A comparison of provider payment adjustments across 20 countries. Issue 5 (May 2022) - Waitzberg, Ruth; Gerkens, Sophie; Dimova, Antoniya; Bryndová, Lucie; Vrangbæk, Karsten; Jervelund, Signe Smith; Birk, Hans Okkels; Rajan, Selina; Habicht, Triin; Tynkkynen, Liina-Kaisa; Keskimäki, Ilmo; Or, Zeynep; et al.
Highlights: Public payers assumed most of the COVID-19-related financial risk. Income loss was not a problem when providers were paid by salary, capitation or budgets. Providers paid based on activity were compensated through budgets or higher fees. New FFS payments were introduced to incentivize remote services. Payments for COVID-19 related costs included new fees, per-diem and DRG tariffs. Abstract: Provider payment mechanisms were adjusted in many countries in response to the COVID-19 pandemic in 2020. Our objective was to review adjustments for hospitals and healthcare professionals across 20 countries. We developed an analytical framework distinguishing between payment adjustments compensating income loss and those covering extra costs related to COVID-19. Information was extracted from the Covid-19 Health System Response Monitor (HSRM) and classified according to the framework. We found that income loss was not a problem in countries where professionals were paid by salary or capitation and hospitals received global budgets. In countries where payment was based on activity, income loss was compensated through budgets and higher fees. New FFS payments were introduced to incentivize remote services. Payments for COVID-19 related costs included new fees for out- and inpatient services but also new PD and DRG tariffs for hospitals. Budgets covered the costs of adjusting wards, creating new (ICU) beds, and hiring staff. We conclude that public payers assumed most of the COVID-19-related financial risk. In view of future pandemics policymakers should work to increase resilience of payment systems by: (1) having systems in place to rapidly adjust payment systems; (2) being aware of the economic incentives created by these adjustments such as cost-containment or increasing the number of patients or services, that can result in unintended consequences such as risk selection or overprovision of care; and (3) periodically evaluating the effects of payment adjustments on access and quality of care.